THE BOUNDARY BETWEEN NEMAKIT-DALDYNIAN AND TOMMOTIAN STAGES (VENDIAN-CAMBRIAN SYSTEMS) OF SIBERIA - Khomentovsky V.V.; Karlova G.A. (My University, 2002)
Distribution of small shelly fossils (SSF) in the Tommotian and upper Nemakit-Daldynian stages is revised in all main reference sections of the Siberian platform, particularly in its eastern facies zone. Correlation of coeval sections between each other and with the stratotype section of the transitional facies zone is substantiated in the northern and southeastern parts of the platform. As is shown, boundary between the indicated subdivisions is synchronous, marked by an extremely sharp change in abundance and diversity of SSF assemblages immediately above it. This fact and appearance of macrofaunal remains (archaeocyathids, brachiopods) imply that the Tommotian Stage exemplifies one of the most important phases in evolution of skeletal fauna. The boundary is also marked by a sharp negative excursion in the δ13C curve. The obtained data on the lower boundary of the Tommotian Stage and its isotopic characteristic enable its global correlation and allow it to be accepted the lower boundary of the Cambrian System. The correlation method based on SSF assemblages and applied to different-facies Tommotian sequences is modified. It is important to analyze all local fossil assemblages and occurrence levels of younger taxa when substantiating boundaries of stratigraphic units instead of a limited number of guide species. Only this method enables recognition of age analogues of the Tommotian Stage subdivisions in the eastern and transitional zones.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская